2019
DOI: 10.1155/2019/5231219
|View full text |Cite|
|
Sign up to set email alerts
|

Uterine Tumor Resembling Ovarian Sex Cord Tumors Type II with Vaginal Vault Recurrence

Abstract: UTROSCTs (Uterine Tumors Resembling Ovarian Sex Cord Tumors) are rare neoplasms of unknown etiology usually occurring in middle-aged women. Less than 100 cases of UTROSCT have been reported so far. Although the typical behavior of UTROSCT is benign, metastatic and recurrent cases can occur. Here we describe an extremely rare case of vaginal vault recurrence of UTROSCT occurring 5 years after total hysterectomy with bilateral salpingo-oophorectomy. Though rare, UTROSCT should always be taken into account in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Neither the size (ranging from 1 to 20 cm), nor the relationship to the myometrium (whether submucosal or intramural) or endometrium (such as polypoid intracavitary growth), facilitates the differentiation of UTROSCT from myomas or polyps. Additionally, it is noteworthy that UTROSCT often coexists with one or more leiomyomas in the same patient [18,27,41,103].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither the size (ranging from 1 to 20 cm), nor the relationship to the myometrium (whether submucosal or intramural) or endometrium (such as polypoid intracavitary growth), facilitates the differentiation of UTROSCT from myomas or polyps. Additionally, it is noteworthy that UTROSCT often coexists with one or more leiomyomas in the same patient [18,27,41,103].…”
Section: Discussionmentioning
confidence: 98%
“…The coexistence of UTROSCT with other tumors at the time of surgery was not unusual, mostly with typical leiomyomas [18,27,[41][42][43]45,48,60,103], but also with other neoplasms such as a second UTROSCT [29,60], ovarian sex cord stromal tumors [41], gastrointestinal stromal tumors [94], endometrial adenoacanthoma [17], cervical intraepithelial neoplasia [120], or cervical metastasis from breast cancer [40].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In fact, although, UTROSCT usually exhibits benign behavior with a favorable prognosis, this neoplasm is classified as being of uncertain malignant potential, given its low rate of recurrence and the fact that it can sometimes cause metastases. In table 1 we have summarized the cases of UTROSCT which we found in literature from 1986 to 2023, that recurred or caused metastases and occasionally also death [19,20,30,31,36, (Table 1 From our review we observed that many cases with UTROSCT, which recurred or developed metastases, were observed in single case reports [31,35,[42][43][44][46][47][48][49][52][53][54][55]58,59] or sometimes in very small case series [19,30,40,45,50,57] (Table 1). The most frequent sites of recurrences or metastases in these cases were lymph nodes, peritoneum, omentum, vaginal vault, lung, and liver [44][45][46]49,[52][53][54][55].…”
Section: Clinical Datamentioning
confidence: 99%
“…These are considered to have low malignant potential. [1][2][3] UTROSCTs are mostly surgically : A total of 701 histologic diagnoses comprised of benign, precursor, and malignant lesions and accounted for 86.6%, 2.6%, and 10.8% respectively with preponderance in females. The common benign lesions included melanocytic nevus (17.7%), epidermal cyst (11%), hemangioma (8.9%), dermoid cyst (8.2%), chalazion (6.7%), and squamous papilloma (6.4%).…”
Section: Introductionmentioning
confidence: 99%